Nomenclature of African species of the genus Stenodactylus (Squamata: Gekkonidae) - Metallinou, Margarita; Crochet, Pierre-André (Zootaxa, 2013)
The statuses of proposed nomina of the North African species of the genus Stenodactylus have been revised based on the study of their original descriptions and the examination of their name-bearing types. Important nomenclatural actions proposed include the designation of a lectotype for the nomen Stenodactylus guttatus ensuring continuity of the prevailing usage of S. petrii, and the proposal of maintaining prevailing usage of Stenodactylus sthenodactylus by applying to the International Commission of Zoological Nomenclature to set aside the existing name-bearing type and replace it with a neotype corresponding with that usage.